Composição bromatológica e perfil fermentativo da silagem de soja com diferentes inclusões de milho moído - Duarte, Andressa (2023)
The objective of this work was to evaluate the effects of adding ground corn to soybean silage on fermentative parameters and chemical composition. Four treatments were used with different levels of ground corn (0%, 6%, 12% and 18%) based on dry matter. The silages were stored in PVC mini silos and opened after 1, 3, 7, 15, 30, 60 and 90 days of ensiling. At opening, silage samples were collected for analysis of fermentation parameters (pH, NH3-N, organic acids), chemical composition (dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), in vitro dry matter digestibility (DIVMS)) and microbial counts (clostridia, aerobic mesophiles, lactic acid bacteria, Listeria spp, enterobacteria, molds and yeasts). The experimental design was completely randomized in a split-plot arrangement, with 4 replications per treatment. When there was interaction between the factors, the effects were analyzed by means of orthogonal polynomials. A significant result was considered when the p-value was less than or equal to 5%. The results showed that the inclusion of ground corn linearly increased the dry matter content of the silages. Silage pH and NH3-Ndecreased as ground corn level increased. Lactic and acetic acids and in vitro dry matter digestibility increased linearly with ground corn addition Counts of enterobacteria and yeasts were low and lactic acid bacteria and clostridia reduced over time. The inclusion of ground corn also linearly increased the crude protein and neutral detergent fiber contents of the silages but reduced the acid detergent fiber contents. In conclusion, the inclusion of ground corn on improves the fermentative parameters and the chemical composition of soybean silage.